Proximal type epithelioid sarcoma of the scrotum: A source of diagnostic confusion that needs immediate attention - TANIDIR, YILÖREN (ELSEVIER SCIENCE BV, 2006)
Epithelioid sarcoma is a rare soft-tissue sarcoma which classically presents as a subcutaneous or deep dermal mass in distal extremities of adolescents and young adults. A more aggressive proximal or large-cell type has been described in rare cases to occur as a deep soft-tissue mass at proximal body sites which tends to recur and metastasize earlier than the conventional epithelioid sarcoma. The correct diagnosis of this type is essential since these lesions can easily be misdiagnosed as other epithelioid lesions. Its prognostic factors also have not yet been fully investigated. We herein report a case of metastatic proximal-type epithelioid sarcoma arising from the scrotum of a 50-year-old man managed by radical surgery and adjuvant chemotherapy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: proximal-type epithelioid sarcoma; differential diagnosis; immunohistochemistry; surgery; chemotherapy